Revision of the Chinese endemic subgenus Tschitscherinea Berg, with descriptions of three new species (Coleoptera, Carabidae) - Yin, Wen-Qi; Chen, Jia-Heng; Shi, Hong-Liang (Zootaxa, 2024)
The subgenus Tschitscherinea Berg, 1898 of the genus Pterostichus is reviewed with eight species recognized. Three new species are described: Pterostichus (Tschitscherinea) spissipedes sp. nov. (type locality: Laojunshan, Yunnan, N26.63°, E99.72°), P. (T.) spectabilis sp. nov. (type locality: Luguhu, Yunnan, N27.63°, E100.82°), P. (T.) jiuzhaiicus sp. nov. (type locality: Jiuzhaigou, Sichuan). A new subgeneral synonym is proposed: Jedlickaia Sciaky, 1997 is a junior synonym of Tschitscherinea Berg, 1898 syn. nov. All eight species of the subgenus are keyed, described and illustrated. Pterostichus (Morphohaptoderus) parvicollis Sciaky & Wrase, 1997, a species showing morphological similarities to the subgenus Tschitscherinea, is described and illustrated based on the newly reported male specimen.